2018
DOI: 10.1002/ldr.3071
|View full text |Cite
|
Sign up to set email alerts
|

Sewage sludge as an organic amendment for quarry restoration: Effects on soil and vegetation

Abstract: Quarry restoration in Mediterranean environments usually needs organic amendments to improve the substrates used for technosol construction. Digested sewage sludges from municipal wastewater treatment plants are rich in organic matter, N, and P and constitute an available and economically interesting alternative for substrate amendment. However, their pollutant burden and labile organic matter content involve an environmental risk that must be controlled. Moreover, ecological succession in restored areas can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Therefore, stabilized sludge can be safely used in agriculture. Also, environmental risk involved was pointed out by Carabassa et al [7], who concluded that nitrate inflow to surface water reservoirs may lead to uncontrolled eutrophication. Fortunately, due to the intense nitrate uptake by plant roots during the growing season, this risk may only occur within the first four months after the sludge has been applied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, stabilized sludge can be safely used in agriculture. Also, environmental risk involved was pointed out by Carabassa et al [7], who concluded that nitrate inflow to surface water reservoirs may lead to uncontrolled eutrophication. Fortunately, due to the intense nitrate uptake by plant roots during the growing season, this risk may only occur within the first four months after the sludge has been applied.…”
Section: Resultsmentioning
confidence: 99%
“…Sludge management includes the following methods e.g., landfilling, thermal processes, application to agricultural land, composting, wasteland reclamation and silviculture, use in the construction industry or recovery of rare earth metals [1,[4][5][6][7][8][9][10]. In 2014, total sewage sludge generated in Poland from industrial and municipal wastewater treatment plants was 967.4 thous.…”
Section: Introductionmentioning
confidence: 99%
“…However, we only considered the first top 20 cm of soil in our carbon stock estimations. Consequently we underestimated the total SOC, especially on amended plots, due to the strong plant growth in the first years after Technosol construction (Carabassa et al ). This plant growth, which included trees, could have increased deep C through root growth, as shown by Simón et al () in mine Technosols in SE Spain 6 years after their establishment.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, sludge‐amended Technosols still presented high N and P concentrations after 10 years, and in the specific case of N, more than in the short term after sludge amendment. Although nitrogen leaching is plausible with the sludge treatment, it would mainly take place during the first 4 months due to the high mineralization rates of organic N from sludge (Carabassa et al ). After this period, leaching should decrease quickly due to reduced sludge decomposition rates and the enhanced nitrate absorption by the growing vegetation (Tarrasón et al ; Jordán et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation